2011
DOI: 10.5007/2175-7925.2010v23n2p183
|View full text |Cite
|
Sign up to set email alerts
|

<b>Modelos experimentais para indução de cirrose hepática em animais: Revisão de literatura</b><br>doi: 10.5007/2175-7925.2010v23n2p183

Abstract: ResumoO fígado desempenha papel homeostático fundamental no equilíbrio de numerosos processos biológicos. Cirrose hepática é uma síndrome, na qual convergem algumas doenças hepáticas crônicas, ocorrendo lesão hepatocelular seguida de deposição exacerbada de tecido fibroso ocasionando desorganização da arquitetura tecidual. O fígado está sujeito à lesão potencial por uma grande quantidade de agentes farmacológicos, tóxicos e/ou microbiológicos. Para o estudo de possíveis tratamentos para a cirrose, é necessário… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Chronic liver disease and liver fibrosis have always been the focus of contemporary medical research, and people have tried to establish a model of liver fibrosis to adapt to contemporary research needs in recent years ( Sepanlou et al, 2020 ). As a potent hepatotoxin, TAA-induced liver fibrosis is a well-recognised model for the development of liver damage, regenerative nodules and fibrosis, similar to human liver fibrosis ( Passos et al, 2010 ; Nascimento et al, 2018 ). Numerous experiments have shown that long-term administration of TAA leads to proliferative liver nodules, liver fibrosis, hepatocellular adenomas and hepatocellular carcinoma ( Li et al, 2002 ; Yeh et al, 2004 ; Constantinou et al, 2007 ; Jantararussamee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver disease and liver fibrosis have always been the focus of contemporary medical research, and people have tried to establish a model of liver fibrosis to adapt to contemporary research needs in recent years ( Sepanlou et al, 2020 ). As a potent hepatotoxin, TAA-induced liver fibrosis is a well-recognised model for the development of liver damage, regenerative nodules and fibrosis, similar to human liver fibrosis ( Passos et al, 2010 ; Nascimento et al, 2018 ). Numerous experiments have shown that long-term administration of TAA leads to proliferative liver nodules, liver fibrosis, hepatocellular adenomas and hepatocellular carcinoma ( Li et al, 2002 ; Yeh et al, 2004 ; Constantinou et al, 2007 ; Jantararussamee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical procedures are developed through the administration of hepatotoxic substances. Among several experimental models of cirrhosis induction, TAA, a drug originally used as a fungicide to protect oranges against deterioration and later recognized as a potent hepatotoxin, has been the most promising because it produces macroscopic and histological morphological patterns similar to cirrhosis in human beings (Passos et al 2010).…”
Section: Macroscopic and Histological Assessmentmentioning
confidence: 99%
“…A repetição de um dano tóxico ao fígado é uma estratégia clássica para indução de fibrose e cirrose hepática em animais experimentais (Starkel e Leclercq, 2011). As principais drogas utilizadas para tal fim incluem D-galactosamina, tetracloreto de carbono (CCl 4 ), tioacetamida (TAA) e dimetilnitrosamina (DMN), entre outras, que são administradas por via oral ou por injeção intraperitoneal em diferentes concentrações e em aplicações que podem ser únicas ou semanais com duração de meses (Passos et al, 2011;Tunon et al, 2009).…”
Section: -Modelos Animais De Fibrose E Cirrose Hepáticaunclassified